BLENDING ISLAMIC MICROFINANCE AND PRODUCTIVE ZAKAT TO SUPPORT SDGS IN FISHERIES SECTOR - Kevin Joan; Bambang Catur Pambudi; Dimas Putra Adjie (Jurnal Internasional Ekonomi Islam, 2019)
This paper attempts to offer a viable alternative model to tackle credit distribution problems by using integration of the credit distribution strategy between the financial institutions and amil zakat institution based on kafalah contract. The extant literature on the (i) financing constraints faced by fishermen, and (ii) quadruple helix strategy have been reviewed critically and used in the attempt of proposing an alternative model. The paper has developed blending strategy of Islamic microfinance and productive zakat as a source of financing for fishermen in coastal areas. This model is expected to provide fishermen to meet their liquidity constraint in developing their business. The paper is based on conceptual explorations of literature in the area of Islamic microfinance and zakat. This is a conceptual paper, so it did not employ any empirical analysis. The findings of this paper will provide strategy to optimize fishermen’s business which will increase their prosperity.